The views of stakeholders on the role of the primary school in preventing childhood obesity: a qualitative systematic review. Issue 12 (12th July 2013) - Clarke, J.; Fletcher, B.; Lancashire, E.; Pallan, M.; Adab, P.
Summary: Schools are increasingly recognized as an ideal setting for interventions to tackle childhood obesity. A better understanding of the views of key stakeholders would help to engage schools and inform the feasibility of such interventions in practice. This meta‐synthesis of 18 qualitative studies explores the views of parents, school staff, school governors, school nurses and students on the role of the primary school in preventing childhood obesity. Six categories emerged: 'School as a key setting'; 'What schools should be doing to promote healthy eating (HE)'; 'What schools should be doing to promote physical activity (PA)'; 'General barriers'; 'Barriers to promoting HE at school'; and 'Barriers to promoting PA at school'. Thirty‐seven finer‐level themes emerged within these categories. Stakeholders agreed on the key role of the primary school as a setting for obesity prevention, the importance of schools providing and promoting opportunities for HE and PA, and the need for schools to work with parents. Some perceived barriers could be overcome at school level, e.g. using unhealthy foods as rewards/fundraisers or withholding PA for bad behaviour. Leadership and guidance from government were considered to be needed to counteract other observed barriers, particularly regarding school canteens, support for parents and time for PA.